Cover Feature: Effect of Second‐Order Spin–Orbit Coupling on the Interaction between Spin States in Spin‐Crossover Systems (Chem. Eur. J. 20/2018). Issue 20 (24th March 2018) - Sousa, Carmen; Domingo, Alex; de Graaf, Coen
Abstract : Higher‐order spin–orbit couplings are calculated with an approach based on effective Hamiltonian theory. This method can be used instead of the perturbational expressions, which are both rather inaccurate and not applicable to estimate the higher‐order spin–orbit coupling between excited states. We show how the combination of geometrical distortions and higher‐order spin–orbit coupling gives rise to a largely increased coupling between spin states that are nearly uncoupled under standard treatment. More information can be found in the Full Paper by C. de Graaf et al. onpage 5146 .